Die Artberechtigung von Macropterna conica Rey (Heteroptera: Lygaeidae). - Wagner, Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1956)
Nomenclatural Acts conica Rey, 1888 (Macropterna), stat. n. hitherto var. of Macropterna convexa Fieber; now a valid species